2023
DOI: 10.5751/es-14443-280417
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning toward “deep” knowledge co-production in coastal and marine systems: examining the interplay among governance, power, and knowledge

Ella-Kari Muhl,
Derek Armitage,
Kevin Anderson
et al.

Abstract: Knowledge co-production (KCP) is presented as an effective strategy to inform responses to complex coastal and marine social-ecological challenges. Co-production processes are further posited to improve research and decision outcomes in a wide range of problem contexts (e.g., biodiversity conservation, climate change adaptation), for example, by facilitating social learning among diverse actors. As such, KCP processes are increasingly centered in global environment initiatives such as the United Nations Decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In practice, addressing knowledge hierarchies starts with acknowledging the influence of researcher positionalities. The provision of a positionality statement alongside research outputs is suggested as best practice to make explicit the context within which knowledge is being produced (Trisos et al, 2021;Muhl et al, 2023). As individuals, we are shaped by our geography, race, gender, sex, ability, spirituality, socioeconomic status, discipline, age, and so much more, which again influences our work, our ways of being and knowing (onto-epistemologies), the intended reader (the gaze), and the standpoint we write from (the pose) (Baker et al, 2019;Trisos et al, 2021).…”
Section: Addressing Research Bias and Positionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, addressing knowledge hierarchies starts with acknowledging the influence of researcher positionalities. The provision of a positionality statement alongside research outputs is suggested as best practice to make explicit the context within which knowledge is being produced (Trisos et al, 2021;Muhl et al, 2023). As individuals, we are shaped by our geography, race, gender, sex, ability, spirituality, socioeconomic status, discipline, age, and so much more, which again influences our work, our ways of being and knowing (onto-epistemologies), the intended reader (the gaze), and the standpoint we write from (the pose) (Baker et al, 2019;Trisos et al, 2021).…”
Section: Addressing Research Bias and Positionalitiesmentioning
confidence: 99%
“…There is also a tendency to transpose Indigenous and local knowledges into the norms of Western-oriented natural science to fit with demands of Governments (Rivers et al, 2023). Such processes commonly aggregate, abstract and alienate knowledge from its holders (Berkes et al, 2000;Latulippe and Klenk, 2020) and assume a lack of interest of knowledge holders in outputs (Mosimege, 2017;Muhl et al, 2023).…”
Section: Integrating Indigenous and Local Knowledge(s)mentioning
confidence: 99%